MiR-34c downregulation leads to SOX4 overexpression and cisplatin resistance in nasopharyngeal carcinoma - Bissey, Pierre-Antoine; Teng, Mona; Law, Jacqueline H.; Shi, Wei; Bruce, Jeff P.; Petit, Valentin; Tsao, Sai W.; Yip, Kenneth W.; Liu, Fei-Fei (BMC cancer, 2020)
Background A major cause of disease-related death in nasopharyngeal carcinoma (NPC) is the development of distant metastasis (DM) despite combination chemoradiotherapy treatment. We previously identified and validated a four microRNA (miRNA) signature that is prognostic for DM. In this study, characterization of a key component of this signature, miR-34c, revealed its role in chemotherapy resistance. Methods Two hundred forty-six NPC patient biopsy samples were subject to comprehensive miRNA profiling and immunohistochemistry (IHC). Two human normal nasopharyngeal cell lines (immortalized; NP69 and NP460), as well as the NPC cell line C666–1, were used for miR-34c gain-of-function and loss-of-function experiments. Signaling pathways were assessed using quantitative real-time PCR (qRT-PCR) and Western blot. Cell viability was measured using the ATPlite assay. Results MiR-34c was downregulated in NPC patient samples, and confirmed in vitro to directly target SOX4, a master regulator of epithelial-to-mesenchymal transition (EMT). MiR-34c downregulation triggered EMT-representative changes in NP69 and NP460 whereby Snail, ZEB1, CDH2, and SOX2 were upregulated, while Claudin-1 and CDH1 were downregulated. Phenotypically, inhibition of miR-34c led to cisplatin resistance, whereas miR-34c over-expression sensitized NPC cells to cisplatin. TGFβ1 decreased miR-34c and increased SOX4 expression in vitro. The TGFβ receptor 1 inhibitor SB431542 reduced SOX4 expression and increased cisplatin sensitivity. Finally, IHC revealed that lower SOX4 expression was associated with improved overall survival in chemotherapy-treated NPC patients. Conclusion miR-34c is downregulated in NPC. Repression of miR-34c was shown to increase SOX4 expression, which leads to cisplatin resistance, while TGFβ1 was found to repress miR-34c expression. Taken together, our study demonstrates that inhibition of the TGFβ1 pathway could be a strategy to restore cisplatin sensitivity in NPC.